Information Seeking Behaviour among Millennial Students in Higher Education - Mohamed Shuhidan, Shamila; Wan Yahya, Wan Aida; Abd Hakim, Azma Asnawishah; Wan Yahya, Husain Hashim; Mohamed Shuhidan, Shuhaida; Anwar, Norizan (UiTM Press, 2020)
This paper investigates various information seeking behaviour demonstrated by millennial students in higher education. The impact of disruptive technology changes the students’ information seeking behaviour as millennial students nowadays depend on the Internet too much to locate the information for their academic purposes. Studies also found that millennial students have difficulty in learning and were marked by uncertainty because they are facing information overload, inability to obtain and evaluate the information. Identifying and recognising appropriate information seeking processes is crucial in determining the effectiveness of the information- seeking behaviour and the quality of the information gathered in order to support their learning process and experience. Therefore, this paper focuses on the behaviour applied by these students to fulfil demands of academic compliance especially in efforts to seek research-based information.About 328 students took part in this online survey. Findings of this research use quantitative descriptive analysis. From the findings, respondents claim that they are familiar with information seeking processes with mean value is 3.63, however 30.5% respondents claim they still lacking in information seeking skills. This research provides a valuable insight regarding the information seeking behaviour of millennial students and make a recommendation that role of modern libraries should facilitated this demand by ensuring that services such as online library resources are accessible and set-up for use by the millennial students.